Fully understanding the positive roles of plasmonic nanoparticles in ameliorating the efficiency of organic solar cells. Issue 37 (1st September 2015) - Chi, Dan; Lu, Shudi; Xu, Rui; Liu, Kong; Cao, Dawei; Wen, Liaoyong; Mi, Yan; Wang, Zhijie; Lei, Yong; Qu, Shengchun; Wang, Zhanguo
Abstract : This paper provides a comprehensive perspective on the roles of plasmonic particles in organic solar cells and insights into the photo energy conversion process in the plasmonic surroundings. Abstract : Herein, we constructed inverted PBDTTT-CF:PC70 BM bulk-heterojunction organic solar cells by introducing Au nanoparticles to a ZnO buffer layer and a great improvement in energy conversion efficiency has been realized. To discover the positive roles of such plasmonic nanoparticles in the process of solar energy conversion, photovoltaic devices with the same architecture but different sized Au nanoparticles were purposely fabricated and it has been observed that the overall efficiency can be remarkably improved from 6.67% to 7.86% by embedding 41 nm Au nanoparticles in the buffer layer. The devices with other sizes of Au nanoparticles show a relatively low performance. Subsequent investigations including finite difference time domain simulation and transient photoluminescence studies reveal that the existence of the plasmonic particles could not only improve the optical absorption and facilitate the exciton separation, but can also benefit the collection of charge carriers. Thus, this paper provides a comprehensive perspective on the roles of plasmonic particles in organic solar cells and insights into the photo energy conversion process in the plasmonic surroundings.